DAMPAK PENAMBANGAN EMAS TANPA IZIN (PETI) TERHADAP MAKROZOOBENTOS DI PERAIRAN SUNGAI BODI, DESA BODI, KECAMATAN PALELEH BARAT KABUPATEN BUOL, PROVINSI SULAWESI TENGAH - Maming; Radianti Yahya Douw; Amir Yassi (Universitas Hasanuddin, 2021)
ABSTRACT Unlicensed Gold Mining (PETI) Effect on Macrozoobentos in The Waters of The Bodi River, Western Paleleh District, Buol District, Central Sulawesi Province, in addition to damaging the environment, also endangers the lives of miners and the surrounding community, therefore it is necessary to maintain water quality according to its designation. This study aims to determine the quality of the waters of the Bodi River, social and economic conditions, as well as the health condition of the mining community affected by PETI activities. The parameters studied were macrozoobentos ecology index.This research was conducted at 4 sample point stations representing observation locations, each representing Location I (Upstream), Location II (mining activity area), and Location III (settlement). This type of research is an analytic observational study, with a research design using a cross sectional study. Macrozoobentos samples were taken using the Ekman grab. The results showed that the status of the water quality of the Bodi River at Station 1,2,3, and 4 dominance of macrozoobentos indicates unstable, depressed and high dominance water conditions.